Identification of Antioxidant and Antidiabetic Compounds in Hedychium spicatum using TLC Bioautography Coupled with Mass Spectrometry and their in silico Molecular Docking Studies - Singh, Harjeet; Singh, Nardev (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Traditional system of medicine has been practised since a long time to cure various diseases. More than 60-80 percent people across the world use herbal medicine for their health care. In the present study, TLC-MS bioautography combined with DPPH, α-amylase and α-glucosidase bioassay were used to compare antidiabetic and antioxidant activities in hydro alcoholic extracts of H. spicatum and also explore in silico molecular docking studies. Materials and Methods: In this paper, hydro-alcoholic extract of H. spicatum was prepared, run TLC and performed TLC- MS bioautography to identify antidiabetic and antioxidant bioactive compounds. Results: HPTLC analysis showed there are 10 and 5 metabolites present at 254 nm and 366 nm respectively in H. spicatum. Further, TLC-MS bioautography studies isolate total two lead compounds such as quercetin and beta-sitosterol. Quercetin shows DPPH, α-amylase and α-glucosidase activity whereas beta sitosterol shows α amylase activity only. Conclusion: In conclusion, TLC-MS bioautography proved to be a good technique to evaluate the antidiabetic and antioxidant potential of plant extracts and will be useful for discovering new therapeutic regimens.
Keywords: Hedychium spicatum; TLC-bioautography; Antioxidant; Antidiabetic; in silico